2009
DOI: 10.4103/0971-4065.59335
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin converting enzyme gene polymorphism in type II diabetics with nephropathy

Abstract: Nephropathy is an important and a frequent complication of long-term type II diabetic nephropathy. Strong evidence exists that genetic predisposition plays a major role in the development of diabetic nephropathy. Recent studies have implicated association between angiotensin converting enzyme (ACE) insertion/deletion (I/D) gene polymorphism and nephropathy. The deletion gene polymorphism of ACE gene has been shown to be associated with increased activity of this enzyme. This study examines the association of A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 13 publications
0
9
0
Order By: Relevance
“…In support of a genetic etiology for subtype 1 phenotype manifestation, the ACE gene, which encodes angiotensin I converting enzyme and was specifically associated with this cohort (Table 3A and Fig. 2), has been implicated in diabetic nephropathy (52, 53) and also in platelet aggregation (53). Accordingly, this association could reasonably suggest a mechanism to explain the lower platelet counts observed in subtype 1 patients (54).…”
Section: Discussionmentioning
confidence: 69%
“…In support of a genetic etiology for subtype 1 phenotype manifestation, the ACE gene, which encodes angiotensin I converting enzyme and was specifically associated with this cohort (Table 3A and Fig. 2), has been implicated in diabetic nephropathy (52, 53) and also in platelet aggregation (53). Accordingly, this association could reasonably suggest a mechanism to explain the lower platelet counts observed in subtype 1 patients (54).…”
Section: Discussionmentioning
confidence: 69%
“…The association of ACE I/D polymorphism with T2DM risk and related renal and cardiovascular complications has been extensively studied throughout all the major ethnic groups but with highly inconsistent findings. Whereas some have found that the D allele is more common in T2DM and related complications in Tunisian [ 16 ], Indian [ 17 ], and Iranian populations [ 18 ], others have demonstrated no association of either allele with T2DM or related cardiovascular and renal disease in Malay and Indonesians [ 19 – 21 ]. The association between these polymorphisms and the ACE gene is similarly discrepant between its association with hypertension in the Japanese [ 22 ] and its nonassociation in the Chinese [ 23 ].…”
Section: Introductionmentioning
confidence: 99%
“… 7 However, our results are in contrast to previous studies from South India which reported an association of D/D polymorphism with nephropathy in type 2 diabetes subjects. 19 , 20 However, number of participants studied was small in these studies. Another study from Gujarat also found microalbuminuria to be more prevalent in those patients with insulin-dependent diabetes mellitus who had D/D polymorphism.…”
Section: Discussionmentioning
confidence: 96%